Ideologi dan Relasi Kuasa dalam Pemberitaan Kematian Gajah Sumatera: Kajian Analisis Wacana Kritis Teun A. Van Dijk - Apriliani Daely; Aulia Hasanah; Retno Anggelica Aini; Riva Amanda; Shela Jenari Marbun; Dewi Arisnofita (INDO PUBLISHING, 2026)
This study aims to analyze ideology and power relations in the reporting of the death of a Sumatran elephant in Riau using Teun A. Van Dijk's Critical Discourse Analysis model. This study employed a qualitative approach, using data from three purposively selected online news texts. Data collection was conducted through documentation, while data analysis encompassed the text's macrostructure, superstructure, and microstructure, as well as dimensions of social cognition and social context. The results show that the media framed the event as a crime against protected animals and an ecological tragedy. The dominance of official sources reinforced the legitimacy of state institutions, while the use of emotional lexicon and passive voice created a dramatic effect while obscuring the perpetrators. These findings confirm that the reporting is not neutral, but rather represents power relations and specific ideological tendencies in conservation issues.